1989
DOI: 10.1136/bjo.73.11.911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters predictive of enlargement of melanocytic choroidal lesions.

Abstract: SUMMARY The authors followed up 197 melanotic choroidal lesions (62 categorised as benign naevi, 76 classified as suspicious naevi, 41 diagnosed as dormant melanomas, and 18 categorised as active melanomas) left untreated after their initial clinical documentation. Thirty-nine of these lesions enlarged during a five-year follow-up interval (cumulative proportion of lesions that enlarged=26-2% by Kaplan-Meier method). Individual clinical parameters predictive of lesion enlargement (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 5 publications
4
42
0
4
Order By: Relevance
“…A prior study from our department found that tumors located closer to the optic disc had a greater tendency to demonstrate growth; however, metastases was not included as an outcome measure. 24 Choroidal melanomas that show clinical evidence of growth have an increased mitotic activity histopathologically when compared with nongrowing tumors.4' Mitotic activity has long been associated with malignant potential.3 We found in our study that documented tumor growth carried a substantial relative risk of 7.6 for development of metastases as compared with nongrowing lesions. Because ofthe prominent risk for metastases in growing tumors, we sought to identify the factors that predicted tumor growth.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…A prior study from our department found that tumors located closer to the optic disc had a greater tendency to demonstrate growth; however, metastases was not included as an outcome measure. 24 Choroidal melanomas that show clinical evidence of growth have an increased mitotic activity histopathologically when compared with nongrowing tumors.4' Mitotic activity has long been associated with malignant potential.3 We found in our study that documented tumor growth carried a substantial relative risk of 7.6 for development of metastases as compared with nongrowing lesions. Because ofthe prominent risk for metastases in growing tumors, we sought to identify the factors that predicted tumor growth.…”
Section: Discussionsupporting
confidence: 56%
“…[23][24][25][26] Most recently, Butler and coworkers26 studied "indeterminate" pigmented choroidal tumors and identified risk factors for tumor enlargement, including greater tumor thickness, symptoms, orange pigment, internal quiet zone on B-scan ultrasonography, and hot spots of fluorescein angiography. Of the 195 tumors in their series without documented growth, there were no metastases, and of the 98 tumors demonstrating growth, 5% developed metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta forma de raciocínio, entretanto é contrária à filosofia aplicada para os cânceres em geral que preconiza o diagnóstico e tratamento precoce com intuito de aumentar a sobrevida dos pacientes. O curso natural destas pequenas lesões melanocíticas da coróide vem sendo estudado e fatores preditivos de crescimento vêm sendo definidos, porém atualmente, mais do que a preocupação com o crescimento destas lesões, estudos vem sendo conduzidos com o objetivo de definir seu potencial de desenvolver doença metastática e morte (11)(12)(13)(14)(15)(16) . Diener-West e col. encontraram uma taxa de mortalidade de 16% em 5 anos para portadores de tumores da coróide classificados como pequenos, e demonstraram que indivíduos com melanomas da coróide pequenos apresentam um risco de óbito 1,3 vezes maior quando comparados à população geral (13) .…”
Section: Discussionunclassified
“…This difficult situation is rather different from that of medium-sized and large melanomas, which can be diagnosed correctly in more than 99% of cases [2] . Clinical features predictive of tumour growth were described over twenty years ago and include: tumour thickness exceeding 2 mm; confluent orange pigment; serous retinal detachment; symptoms (blurred vision or loss of peripheral vision, floaters or flashing lights); and contact with optic disc [3,4] . The likelihood of tumour growth is related to the number of such risk factors that are present.…”
Section: Introductionmentioning
confidence: 99%